A Meta‐Analysis of Research on the Read Aloud Accommodation. Issue 3 (September 2014) - Buzick, Heather; Stone, Elizabeth
<x xml:space="preserve">Abstract</x> Read aloud is a testing accommodation that has been studied by many researchers, and its use on K‐12 assessments continues to be debated because of its potential to change the measured construct or unfairly increase test scores. This study is a summary of quantitative research on the read aloud accommodation. Previous studies contributed information to compute average effect sizes for students with disabilities, students without disabilities, and the difference between groups for reading and mathematics using a random effects meta‐analytic approach. Results suggest that (1) effect sizes are larger for reading than for math for both student groups, (2) the read aloud accommodation increases reading test scores for both groups, but more so for students with disabilities, and (3) mathematics scores gains due to the read aloud accommodation are small for both students with and without disabilities, on average. There was some evidence to suggest larger effects in elementary school relative to middle and high school and possible mode effects, but more studies are needed within levels of the moderator variables to conduct statistical tests.